2016
DOI: 10.1002/aenm.201600116
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Disulfide/Nitrogen‐Doped Reduced Graphene Oxide Nanocomposite with Enlarged Interlayer Spacing for Electrocatalytic Hydrogen Evolution

Abstract: Facile design of low‐cost and highly active catalysts from earth‐abundant elements is favorable for the industrial application of water splitting. Here, a simple strategy to synthesize an ultrathin molybdenum disulfide/nitrogen‐doped reduced graphene oxide (MoS2/N‐RGO‐180) nanocomposite with the enlarged interlayer spacing of 9.5 Å by a one‐step hydrothermal method is reported. The synergistic effects between the layered MoS2 nanosheets and N‐doped RGO films contribute to the high activity for hydrogen evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
265
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 463 publications
(287 citation statements)
references
References 50 publications
21
265
1
Order By: Relevance
“…[140] Recent DFT calculation reveals that ∆G H value of MoS 2 can be reduced by 0.149 eV to achieve a more preferable value of −0.052 eV when the interlayer spacing is increased from 0.62 nm of ordinary MoS 2 nanosheets to 0.95 nm of expanded MoS 2 nanosheets (Figure 11A). [43] It suggests that interlayer expansion can provide MoS 2 nanosheets with faster proton/ electron adsorption and hydrogen release processes, which are preferable for high HER activity. As a typical example, Sun et al reported a microwave-assistant solvothermal method to synthesize MoS 2 nanostructures with an expanded interlayer spacing of 0.94 nm at temperatures ranging from 190 to 260 °C for HER application ( Figure 11B,C).…”
Section: Applications As Electrocatalysts For Hydrogen Evolution Reacmentioning
confidence: 99%
See 4 more Smart Citations
“…[140] Recent DFT calculation reveals that ∆G H value of MoS 2 can be reduced by 0.149 eV to achieve a more preferable value of −0.052 eV when the interlayer spacing is increased from 0.62 nm of ordinary MoS 2 nanosheets to 0.95 nm of expanded MoS 2 nanosheets (Figure 11A). [43] It suggests that interlayer expansion can provide MoS 2 nanosheets with faster proton/ electron adsorption and hydrogen release processes, which are preferable for high HER activity. As a typical example, Sun et al reported a microwave-assistant solvothermal method to synthesize MoS 2 nanostructures with an expanded interlayer spacing of 0.94 nm at temperatures ranging from 190 to 260 °C for HER application ( Figure 11B,C).…”
Section: Applications As Electrocatalysts For Hydrogen Evolution Reacmentioning
confidence: 99%
“…Improvement of electrical conductivity by intercalation of conductive NH 4 + ions into MoS 2 interlayers is considered to be responsible for the excellent HER performance. [141] Other examples of HER applications of interlayer-expanded MX 2 include 3D radially oriented MoS 2 nanospheres with an interlayer spacing of 0.707 nm, [98] vertically aligned Li-intercalated MoS 2 nanofilm with an interlayer spacing of 0.721 nm, [51] hollow structured MoS 2 micro/ nanospheres with an interlayer spacing of 0.78 nm, [142] MoS 2 nanoflowers assembled by amorphous nanosheets with an interlayer spacing of 0.80 nm, [143] multiphasic 1T/2H MoS 2 with an interlayer spacing of 0.93 nm, [93] oxygen-incorporated MoS 2 ultrathin nanosheets with an interlayer spacing of 0.95 nm, [77] MoS 2 /N-doped rGO nanocomposite with an interlayer spacing of 0.95 nm, [43] MoS 2x Se 2(1−x) nanotubes with an interlayer spacing of 0.98 nm, [144] MoS 2 nanosheets with an interlayer spacing of 1.01 nm, [145] 1T-MoSe 2 nanosheets with an interlayer spacing of 1.17 nm [82] and 1T-MoS 2 nanosheets with an interlayer spacing of 1.18 nm. [128] Poor intrinsic conductivity of semiconducting MX 2 suppresses the overall HER performance.…”
Section: Applications As Electrocatalysts For Hydrogen Evolution Reacmentioning
confidence: 99%
See 3 more Smart Citations